2020
DOI: 10.1111/tan.13882
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule real‐time DNA sequencing of the full HLA‐E gene for 212 reference cell lines

Abstract: We have developed a genotyping assay that produces fully phased, unambiguous HLA-E genotyping using Pacific Biosciences' single molecule real-time DNA sequencing. In total 212 cell lines were genotyped, including the panel of 107 established at the 10th International Histocompatibility Workshop. Our results matched the previously known HLA-E genotype in 94 (44.3%) cell lines, in all cases either improving or equalling previous genotyping resolution. Three (1.4%) cells had discrepant HLA-E genotyping data and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Moreover, this 28 bp sequence has also been observed repeated four times in another HLA-E allele (HLA-E*01:03:02:07) as described previously. 11 We found the combined frequency in this cohort of HLA-E*01:01 and HLA-E*01:03 alleles was 97.5%, which is in line with the previously published data. 7,8,16 It should be noted however, that as this cohort is not a random population sample we acknowledge that allele frequencies presented from this cohort do not necessarily represent the true frequencies in populations.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, this 28 bp sequence has also been observed repeated four times in another HLA-E allele (HLA-E*01:03:02:07) as described previously. 11 We found the combined frequency in this cohort of HLA-E*01:01 and HLA-E*01:03 alleles was 97.5%, which is in line with the previously published data. 7,8,16 It should be noted however, that as this cohort is not a random population sample we acknowledge that allele frequencies presented from this cohort do not necessarily represent the true frequencies in populations.…”
supporting
confidence: 93%
“…The historical dogma in HLA of only sequencing exons 2 and 3 of class I genes has likely compounded the apparent lack of genetic diversity in HLA‐ E, influencing the most published studies to only sequence exons 2 and 3 and therefore only obtaining second field resolution HLA‐E genotypes. Although exons 2 and 3 are translated into the antigen recognition domain which forms direct molecular interactions with the bound peptide, there is likely to be further genetic polymorphism outside these regions that could be important in immune system related studies, as has been found by ourselves and others with the classical HLA genes 11–13 …”
Section: Assigned Allele Name Closest Allele Genomic Dna Mismatch Gen...mentioning
confidence: 96%
See 2 more Smart Citations
“…In this latter study HLA-E was typed for over 2.5 million potential stem cell donors worldwide and although only a limited 535 bp amplicon (including last part of exon 2, intron 2 and first part of exon 3) was sequenced, it has caused an explosion of new HLA-E alleles (209). Also full length sequencing of HLA-E was developed using both Sanger sequencing (210,211) and NGS (212)(213)(214)(215)(216). These full length strategies have also revealed new alleles, including alleles with polymorphism present outside of the peptide binding groove.…”
Section: Non-classical Hla Class I Determinationmentioning
confidence: 99%